Performance evaluation of the alere PIMA CD4 test for monitoring HIV-infected individuals in resource-constrained settings - Kasama Sukapirom (2018)
Background: Enumeration of CD4+ T-lymphocytes is important in the management of HIV. However, standard laboratory systems based on flow cytometry are expensive, complicated, and thus unavailable to most resource-limited settings where a low-cost and fully automated point-of-care CD4 testing system is required. In attempts to address this issue, a study was conducted to validate the Alere PIMA point-of-care CD4 test. Method: Duplicate values of the absolute number of CD4+ T-lymphocytes in 203 HIV-infected blood samples obtained using the PIMA system were compared with the two predicate single-platform FACSCount and the dual-platform FACSCan (Becton Dickinson Biosciences). RESULTS:: The overall absolute CD4+ T-lymphocyte count obtained using the PIMA system correlated highly with the FACSCount (r 2 = 0.957; mean bias,-54.2 cells/μL; limit of agreement,-190.9 to +82.5 cells/μL) and the FACSCan (r 2 = 0.957; mean bias-44.0 cells/μL; limit of agreement,-179.7 to +91.6 cells/μL). Good correlation and low biases were also observed for samples with CD4+ T-lymphocyte count ranges of 0 to 200 and 0 to 350 cells/μL. Additionally, there was no significant difference in absolute CD4+ T-lymphocyte counts noted between the duplicate samples using the PIMA system. Conclusions: This new point-of-care product is a simple and reliable system and should contribute significantly to the simplification of performing CD4 testing and thus increase access for patients in resource-limited settings. The inability to obtain values for the frequency (%) of CD4+ T-lymphocyte count is one limitation of the PIMA system, the addition of which would be of value for clinical staging or monitoring in HIV-infected pediatric patients. © 2011 by Lippincott Williams & Wilkins.